Conceptualization of depression amongst older adults in rural Tanzania: a qualitative study. (October 2019) - Howorth, Kate; Paddick, Stella-Maria; Rogathi, Jane; Walker, Richard; Gray, William; Oates, Lloyd L.; Andrea, Damas; Safic, Ssenku; Urasa, Sarah; Haule, Irene; Dotchin, Catherine
ABSTRACT: Background: Depression in older people is likely to become a growing global health problem with aging populations. Significant cultural variation exists in beliefs about depression (terminology, symptomatology, and treatments) but data from sub-Saharan Africa are minimal. Low-resource interventions for depression have been effective in low-income settings but cannot be utilized without accurate diagnosis. This study aimed to achieve a shared understanding of depression in Tanzania in older people. Methods: Using a qualitative design, focus groups were conducted with participants aged 60 and over. Participants from rural villages of Kilimanjaro, Tanzania, were selected via randomized sampling using census data. Topic guides were developed including locally developed case vignettes. Transcripts were translated into English from Swahili and thematic analysis conducted. Findings: Ten focus groups were held with 81 participants. Three main themes were developed: a) conceptualization of depression by older people and differentiation from other related conditions ("too many thoughts, " cognitive symptoms, affective and biological symptoms, wish to die, somatic symptoms, and its difference to other concepts); b) the causes of depression (inability to work, loss of physical strength and independence, lack of resources, family difficulties, chronic disease); c) management of depression (love and comfort, advice, spiritual support, providing help, medical help). Conclusions: This research expands our understanding of how depression presents in older Tanzanians and provides information about lay beliefs regarding causes and management options. This may allow development of culturally specific screening tools for depression that, in turn, increase diagnosis rates, support accurate diagnosis, improve service use, and reduce stigma.